2010
DOI: 10.1038/sj.bjc.6605657
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of CCND1 amplification using plasma DNA as a prognostic marker in oesophageal squamous cell carcinoma

Abstract: BACKGROUND: We aimed to develop a new biomarker to predict cyclin D1 (CCND1) status using plasma DNA in oesophageal squamous cell carcinoma (ESCC) patients. METHODS: We evaluated the ratio of the CCND1 (11q13) dosage to the dopamine receptor D2 (DRD2; 11q22-23) dosage (C/D ratio) as CCND1 copy number. This study was divided into three steps: (1) Determination of a cutoff value for the C/D ratio in test scale; (2) Comparison of the C/D ratio in between plasma samples and cancer tissues in ESCC patients showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…It ranks eighth in order of occurrence worldwide and sixth as the leading cause of death (4,5). china has the highest Ec incidence and mortality rates in the world (1,2,5).…”
Section: Introductionmentioning
confidence: 99%
“…It ranks eighth in order of occurrence worldwide and sixth as the leading cause of death (4,5). china has the highest Ec incidence and mortality rates in the world (1,2,5).…”
Section: Introductionmentioning
confidence: 99%
“…The CCND1 gene is recurrently mutated in ESCC with amplifications reported in 33-46% of patients [62][63][64]. The level of CCND1 in plasma was significantly higher in patients with ESCC than healthy controls [65], also when only patients with superficial ESCC were investigated [66]. Furthermore, the survival was significantly poorer in patients with high CCDN1 levels than in patients with low level.…”
Section: Copy Number Variants In Candidate Genesmentioning
confidence: 99%
“…It has been suggested that ctDNA analysis could also be used for detection of minimal residual disease after surgery [85]. This hypothesis has not been tested in GEC, but a number of studies have confirmed that mutant allele frequencies in ctDNA drop after resection of the tumor for GC [59,72,86] as well as ESCC [57,58,65,66].…”
Section: Monitoring Of Treatment Response and Resistancementioning
confidence: 99%
“…ctDNA analysis of patients with squamous cell carcinoma (SCC) of the esophagus with the use of a 90gene panel was associated with sensitivity of 94% and 75%, respectively, when detecting ≥1 or ≥2 mutant genes, suggesting that ctDNA analysis can help monitor treatment effect in these patients [32]. In multivariate analysis, a higher plasma cyclin D1 (CCND1; 11q13) to dopamine receptor D2 (DRD2; 11q22-23) ratio (C/D ratio) was significantly correlated with worse prognosis [33]. In another study, high concordance of multiple somatic mutations was found between plasma ctDNA and tumor (primary or metastases) DNA (83%-100%).…”
Section: Esophageal Carcinomamentioning
confidence: 99%